SYSTEMATIC ANALYSIS OF FUNDAMENTAL AND CLINICAL RESEARCH, AS JUSTIFICATION FOR THE USE OF ESTROGEN-CONTAINING DRUGS WITH THE PREPARATIONS OF MAGNESIUM AND PYRIDOXINE - O. A. Gromova; O. A. Limanova; I. Yu. Torshin (Акушерство, гинекология и репродукция)
Estrogen-containing preparations are widely used in gynecology today for hormone replacement therapy (HRT), as oral contraceptives (OC) and otherwise. Data obtained in large-scale clinical-epidemiological studies showed that intake of estrogen preparations, even of the so-called low-dose ones is associated with certain side effects and with heightened risk of thromboembolism-associated conditions (ischemic stroke, myocardial infarction), of breast cancer and of mortality from cardiovascular events. Available data indicate that estrogens exert negative influence upon metabolism of vitamin В6 and magnesium. Both micronutrients produce proven positive impact upon human health,reducing, in particular, the risk of ischemic stroke, myocardial infarction and  cardiovascular mortality. Therefore then, part of side effects of estrogen preparations could be eliminated or significantly reduced if HRT and OC are carried out with background intake of magnesium preparations and pyridoxine. This paper presents results of systematic analysis of data from fundamental and clinical-epidemiological studies of the influence of estrogens on metabolism of vitamin В6 and magnesium. Results of the analysis indicate that maintaining adequate levels of magnesium and pyridoxine in the body is indispensable for implementation of physiological effects and prevention of pathological effects of estrogens. Detailed description of molecular mechanisms of the discussed interactions is presented. Promising results of use ofmagnesium preparations and pyridoxine in treatment of estrogen-dependent conditions are shown.